Alleviating bias to enhance sustainable construction dispute management. (10th March 2020) - Li, Keyao; Cheung, Sai On
Abstract: Efficient dispute management contributes to cleaner production of construction works. Alleviating bias has been identified as an effective way to enhance construction dispute settlement so as to improve sustainability level of construction projects. In these regards, this study has two objectives. First, a robust bias conceptualization in construction dispute negotiation is developed. Data on practice of biased behaviors in construction dispute negotiation (CDN) were collected from three sources: i) by self-reflection of disputants; ii) by self-realization of disputants in a dispute negotiation simulation; iii) by observations of dispute resolution third-party neutrals. Consistent taxonomies of bias in CDN were obtained, and these are: preconception, self-affirmation, optimism and interest-oriented. The second objective of the study is to suggest bias minimizing approaches to address the afore-mentioned biases. Bias minimizing approaches were firstly identified from literatures and their usefulness against biased behaviors was evaluated by both the simulation and third-party neutral sample. Three bias minimizing approaches were proposed: strategy-based, attitude-based and process-based. It has been found that strategy-based approach is helpful in dealing with preconception bias and self-affirmation bias. Furthermore, attitude-based approach works to alleviate interest-oriented bias and optimism bias, while process-based approach is suitable for preconception bias and interest-oriented bias minimization. Successfully curtailing the influence of bias would smooth and shorten the dispute resolution processes and save valuable resources that can be better deployed for productive uses. Bias minimization in CDN contributes to sustainability of construction projects in the aspects of economic, environment and social influence. Highlights: Human factor in construction project is an often neglected area notwithstanding human decisions are one of the deciding factors on the efficiency and sustainability of construction projects. Efficient dispute management contributes to cleaner production of construction works. Alleviating bias in construction dispute negotiation (CDN) improves sustainability of construction projects from the economic, environment and social aspects with the benefits derived from effective bias-free dispute resolution. A robust bias conceptualization in construction dispute negotiation (CDN) was developed based on data collected from three sources: i) by self-reflection of disputants; ii) by self-realization of disputants in a dispute negotiation simulation; iii) by observations of dispute resolution third-party neutrals. Three groups of bias minimizing approaches were proposed respective to the bias conceptualization: i) strategy-based approach is helpful in dealing with preconception bias and self-affirmation bias; ii) attitude-based approach works to alleviate interest-oriented bias and optimism bias; and iii) process-based approach is suitable for preconception bias and interest-oriented bias minimization.